A novel PLA/P(3HB-co-4HB)/MWCNT composite featuring enhanced mechanical properties and excellent thermal stability based on elongational rheology. (October 2022) - Li, Xiaolong; Zhu, Chuanbiao; Wang, Hu; Xiao, Yang; Lu, Xiang; Li, Yi; Liu, Zhigang; Tong, Yi; Qu, Jinping
Abstract: Simple melt blending is the most frequently-used strategy to obtain high-performance PLA composites. However, the thermosensitive PLA displays the defects of poor thermostability, high brittleness and low heat deformation temperature (HDT) in traditional melt-plasticizing equipment based on shear flow field (SFF). In this work, PLA/P(3HB-co-4HB) blends were fabricated via melt blending technology based on the melt plasticization equipment of elongational flow field (EFF) and SFF. Subsequently, Multi-Walled Carbon Nanotube (MWCNT) was introduced into PLA/P(3HB-co-4HB) blends to prepare PLA/P(3HB-co-4HB)/MWCNT high-performance alloy in an eccentric rotor extruder based on EFF. The periodic compression and release of the EFF on the melt promoted P(3HB-co-4HB) in-situ fiberization and formed special microstructure, which greatly enhanced the mechanical properties, HDT, thermal stability and crystallization perfection of PLA. The tensile strength, Young's modulus, elongation at break, impact strength and HDT of the blend containing 20 wt% P(3HB-co-4HB) under EFF were 8.7%, 22.5%, 80.9%, 62.5% and 14.8% higher than those under SFF, respectively. In addition, MWCNT was induced to disperse into P(3HB-co-4HB) phase by EFF, and played a 'bridge' role in PLA and P(3HB-co-4HB), thereby obtaining PLA/P(3HB-co-4HB)/MWCNT high-performance alloy with stronger comprehensive performance. The fabricated PLA/P(3HB-co-4HB)/MWCNT alloy provides a reference for preparing biopolymers under EFF and broadens the potential application value of PLA/P(3HB-co-4HB). Highlights: The elongational flow field (EFF) induces in-situ fibrillation of P(3HB-co-4HB) to form special microstructure. The mechanical properties obtained under the EFF are better than those under the shearing flow field. EFF endows the materials with great thermal stability and crystallization perfection. The periodic compression and release in EFF enhance the positive displacement conveying.